Shape-engineerable composite fibers and their supercapacitor application. Issue 4 (12th January 2016) - Kim, Kang Min; Lee, Jae Ah; Sim, Hyeon Jun; Kim, Kyung-Ah; Jalili, Rouhollah; Spinks, Geoffrey M.; Kim, Seon Jeong
Abstract : Due to excellent electrical and mechanical properties of carbon nano materials, it is of great interest to fabricate flexible, high conductive, and shape engineered carbon based fibers. Abstract : Due to excellent electrical and mechanical properties of carbon nano materials, it is of great interest to fabricate flexible, high conductive, and shape engineered carbon based fibers. As part of these approaches, hollow, twist, ribbon, and other various shapes of carbon based fibers have been researched for various functionality and application. In this paper, we suggest simple and effective method to control the fiber shape. We fabricate the three different shapes of hollow, twisted, and ribbon shaped fibers from wet spun giant graphene oxide (GGO)/single walled-nanotubes (SWNTs)/poly(vinyl alcohol) (PVA) gels. Each shaped fibers exhibit different mechanical properties. The average specific strengthes of the hollow, twist, and ribbon fibers presented here are 126.5, 106.9, and 38.0 MPa while strain are 9.3, 13.5, and 5%, respectively. Especially, the ribbon fiber shows high electrical conductivity (524 ± 64 S cm −1 ) and areal capacitance (2.38 mF cm −2 ).